PENGEMBANGAN MODUL BAHASA INDONESIA BERBASIS DIGITAL PADA MATERI TEKS BERITA UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Yudistira, Rendy (Universitas Negeri Padang, 2024)
This research aims to develop an effective and interesting learning module using the SAM (Successive Approximation Model), which consists of three phases: preparation phase, iterative design phase, and iterative development phase. In the preparation phase, information is gathered through analysis of student and teacher needs as well as analysis of media and teaching materials to understand the specific needs that will be accommodated by the module. SAVVY Start activities, including brainstorming, sketching, and prototyping, were carried out to design the initial concept of the module. The iterative design phase aims to design modules that are relevant to students' knowledge, skills and competencies through an iterative approach that improves the quality and effectiveness of the modules. The iterative development phase focuses on developing and refining modules as well as feasibility testing involving material experts, language experts and media experts. Expert validation ensures the module meets standards, provides improvement suggestions for optimization, and improves the visual quality of the module. Implementation of these suggestions aims to increase the effectiveness and attractiveness of the module. Overall, the module is declared suitable for use and is expected to be able to support teaching and learning activities better after paying attention to suggestions from validatorsKeywords: Development, Digital Modules, News Texts